TV medical dramas: assessing the portrayal of public health in primetime - Daniela Zago; Peter Cautero; Enrico Scarpis; Erika Pompili; Gianluca Voglino; Roberta Siliquini; Roberta Siliquini; Silvio Brusaferro; Silvio Brusaferro; Laura Brunelli; Laura Brunelli (Frontiers Media S.A., 2024)
IntroductionThe influence of medical dramas could extend beyond the realm of entertainment and potentially strengthen/orient the knowledge, attitudes and hopefully practice of health professionals and the public, despite often depicting unrealistic medical outcomes and scenarios.MethodsThis study examined the portrayal of public health issues in two popular international medical series, "Grey's Anatomy" and "House, MD," selected for their awards and viewership ratings. Individual episodes were double-rated by clinicians for patient characteristics, public health issues, and infection risk management.Results94 episodes with 286 clinical cases were analyzed. A wide range of conditions and pathologies were depicted, with a focus on acute clinical events, trauma and mental disorders, which contrasts with real-life causes of hospitalization and highlight the dramatization in these series. Public health issues such as organ donation and substance abuse were frequently addressed, but prevention and health promotion received little attention. Proper use of personal protective equipment was mostly observed, although hand hygiene was underrepresented.ConclusionThe study highlights the dual role of medical dramas as an entertainment medium and a potential educational tool. While they can raise awareness and encourage healthier behavior, their portrayal of medical practices and patient care often deviates from reality and can create unrealistic expectations. The influence of these dramas also extends to viewers' perceptions of healthcare and medical professionals, underscoring the need for accurate and responsible portrayal of health issues in the media.